Evaluating the Parsęta Basin Communes’ Tourist Space Using the Selected Quantification Methods - Domin, Dominik Jan; Kwiatkowski, Grzegorz; Chodkowska-Miszczuk, Justyna (Quaestiones Geographicae, 2010)
Identifying differences in the factors determining tourism development in an area is crucial to utilising its natural, economic and socio-cultural resources that enable sustainable development of the tourist function. This article sets out to present and estimate factors underlying tourism development in the context of various quantification methods and the comparisons of their results. The phenomenon selected for the research is evaluated using tools such as a synthetic measure Gołembski (2002) (based on weights assigned to particular features) and two synthetic measures Perkal (z-scores) (1953) and Zioło (1985).